Transport Mechanisms of Polymannuronic Acid and Polyguluronic Acid Across Caco-2 Cell Monolayers - Yu Wang; Xu Bai; Bo Hu; Maochen Xing; Qi Cao; Aiguo Ji; Shuliang Song (MDPI AG, 2020)
Detailed knowledge of the intestinal transport of polymannuronic acid (PM) and polyguluronic acid (PG) is critical for understanding their biological activities. To investigate the transport in the gastrointestinal tract, PM and PG were chemically modified with tyramine and conjugated with fluorescein isothiocyanate (FITC) to synthesize FITC-PM (F-PM) and FITC-PG (F-PG) successfully. The transport mechanisms of F-PM and F-PG across the intestinal epithelial cell monolayers (Caco-2 cell monolayers) were then investigated. The results demonstrated that the transport of F-PM and F-PG into epithelial cells was time- and energy-dependent, which was mediated by the macropinocytosis pathway and the clathrin- and caveolae (or lipid raft)-mediated endocytic pathway. The transport process of F-PM and F-PG in Caco-2 cells depended on the acidification of endosomes and involved lysosomes. Tubulin mediated the transport of F-PM, but not of F-PG. Moreover, the absorption enhancer chitosan (CS) promoted the transport of F-PM and F-PG, increasing the apparent permeability coefficient (Papp) by 1.9-fold and 2.6-fold, respectively, by reversibly opening the tight junction (TJ). In summary, this study provided a comprehensive understanding of the transport of PM and PG in the small intestinal epithelial cells, which will provide a theoretical basis for the development of PM and PG with good intestinal absorption.